Modern High Strength Concrete with Unique Properties - Soloviova, Valentina; Soloviov, Dmitriy; Stepanova, Irina (International Journal of Engineering and Technology, 2018)
Artificial stone has been one of the most common materials in construction for a long time by now. Despite the variety of types of concrete, the composite is in constant motion of development and improvement. The common use of high strength composite is for the construction of high-rise buildings or projects complex in geometry.This article suggests preparing high-strength cementitious composites by complex chemical activation using chemical admixtures in combination with reactive aggregates, as they give good hydration (hardening) of concrete. Research results confirm that this practice of complex chemical activation of cement gives high-strength concrete with better strength, deformation and durability properties.Â